An assessment of water quality and endocrine disruption activities in the Eerste/Kuils River catchment system, Western Cape, South Africa - Fourie, Shani (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc)--University of Stellenbosch, 2005.